Pelaksanaan Supervisi Akademik Berbasis Lesson Study untuk Meningkatkan Kinerja Guru di SMPN 1 Baitussalam: Implementation of Lesson Study-Based Academic Supervision to Improve Teacher Performance at SMPN 1 Baitussalam - Roslina Roslina; Rita Novita; Musdiani Musdiani (Edu Cendikia: Jurnal Ilmiah Kependidikan, 2026)
Low teacher performance in preparing instructional materials and conducting innovative lessons is the primary issue at SMP Negeri 1 Baitussalam, Aceh Besar Regency; the average pre-cycle performance score was only 57.69 (classified as "poor"), a finding corroborated by low scores on the 2024 Teacher Competency Test. This study aimed to analyse the implementation of *Lesson Study*-based academic supervision in enhancing teacher performance across the aspects of lesson planning, implementation, and evaluation. Conducted from January to April 2026, this School Action Research involved five teachers—specialising in Science, Mathematics, and English—who had previously scored below the "good" category; the study employed the Kemmis and Taggart cyclical model integrated with the "plan-do-see" stages. Data were collected through observation and documentation and analysed using descriptive percentage techniques. The results demonstrated significant improvements across all aspects. The ability to prepare lesson plans or teaching modules rose from 57.69 to 72.71 in Cycle I and reached 88.13 in Cycle II. Instructional implementation skills improved from 72.50 to 89.11, while evaluation skills rose from 71.25 to 89.43; both metrics reached the "good" category. Notably, the greatest improvement occurred in the evaluation aspect, indicating that the collective reflection inherent in *Lesson Study* is effective in rectifying areas that were previously the weakest. The study concludes that *Lesson Study*-based academic supervision effectively enhances teacher performance and serves as a relevant model for continuous professional development.